Inflation and the money supply in the United States, 1956-1977 - Berman, Peter I. (Lexington, Mass. : Lexington Books, 1978)
The purpose of this study is to empirically examine whether the money supply has been a continuing source of inflation in the United States over the past two decades.
Includes index.
Bibliography: p. 129-132.
osc 27/4/18
Loans
Keywords: Inflation (Finance); Money supply